Вплив технологічних параметрів обробки розплаву намеханічні властивості ливарних сплавів системи Al-Mg - Кулініч, Андрій; Котляр, Сергій (КІНПАТРІ ЛТД, 2013)
It is set that optimization of temperature and time of self-control in the liquid state allows to promote the level of durability on the break of alloys of АМг6л and АМг11 accordingly on 16 and 21 %. Thus, the values of the relative lengthening of alloys are multiplied in 1,5–3,0 time.It is rotined that increase of cooling speed during crystallization from 0,5 to 4,5 С/с allows to decrease the size of corn of aluminium sosoloid for the alloy of АМг6л in 2 times, and for the alloy of АМг11 in 1,8 times.
Influence of technological parameters of treatment of fusion on mechanical properties of casting alloys of system of Al-Mg